INTERVENTIONS TO REDUCE MENOPAUSE SIGNS AND SYMPTOMS IN MENOPAUSE WOMEN A NARRATIVE REVIEW - Hermayanti, Yanti; Alfilatillatifah, Alfilatillatifah; Arrafi, Almay Rayhan; Arafah, Hilwah Nurul; Fernanda, Ni Putu Mulia; Hidayat, Wahyu; Sismayadi, Zahrul Insan (Journal of Maternity Care and Reproductive Health, 2024)
Introduction: Women who experience menopause will experience a decrease in the hormones estrogen and progesterone that occurs before menopause caused by ovarian atrophy, so it needs to be overcome with pharmacological and non-pharmacological therapy. One type of non-pharmacological therapy is complementary therapy. Objective: This study aims to identify interventions that can be taken to reduce menopausal signs and symptoms. Methods: CINAHL, PubMed, and Sage Journal databases were used for searching articles with sample inclusion criteria of menopausal women, Randomized Controlled Trials or quasi experimental study design, published in 2017-2022, in English, and full text. The exclusion criteria used were the focus of articles discussing interventions to reduce menopausal signs and symptoms with pharmacological therapy, protocol study articles, and pre-proof articles. Results: The search results for 14 matching articles were found. Interventions that can be done to reduce menopausal signs and symptoms are grouped into 4 approaches, namely psychological approaches (self hypnosis and mindfulness stress reduction programs), physical approaches (foot soaking and physical activity), nutritional approaches (herbal medicine, administration of magnesium, fluid nutrition, administration of isoflavones), and combined approaches (electroacupuncture, combined diet guidance and anti-resistance exercises). Conclusions: From the 14 articles obtained, it can be concluded that there are 4 categories of therapeutic approaches that can be taken to reduce menopausal symptoms.It is recommended that further research focus on interventions that are effective in reducing menopausal symptoms.